A Comparative Analysis of Different 3rd Trimester Using Fetal Biometric Parameters- An Ultrasound Study - Bhardwaj, Kamal; Parashar, Radhika; kumar, Sumit; Yadav, Chandramani (Journal of Neonatal Surgery, 2025)
Title- A Comparative Analysis on 3rd Trimester using Different Fetal Biometric parameters-An Ultrasound study Objective- The objective of the study to determine the accuracy of 3rd trimesters for determining gestational age with the help of regression tables formulated to collaborate menstrual age with gestational age. Background- Each examination was performed after the routine antenatal check up by the obstetrician prior to the scan. The patients were explained the procedure and its purpose, prior to scanning. Patient was placed supine and the area between the pubic symphysis and umbilicus was exposed, the ultrasonic jelly was applied to the skin and transducer’s head. The jelly serves to make better contact between the skin surface and the transducer, making the passage of ultrasonic wave easier. Subjects-The Study is being Conducted in 200 normal pregnant females between 29th to 39th weeks of gestation. Methods- All examinations were performed by using a Gray scale real time machine (Sonosite Micromax M Turbo) employing a 3-5 MHz convex transducer. Result- There was significant reduction in overall variability and maximum observed error when multiple fetal parameters were used instead of single parameter. Conclusion and Discussion- Our present study also revealed that the use of multiple fetal parameters results in greater accuracy for gestational age determination.